2017
DOI: 10.1017/ice.2017.181
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Scrub Contamination and Transmission (ASCOT) Trial: A Three-Arm, Blinded, Randomized Controlled Trial With Crossover Design to Determine the Efficacy of Antimicrobial-Impregnated Scrubs in Preventing Healthcare Provider Contamination

Abstract: objective. To determine whether antimicrobial-impregnated textiles decrease the acquisition of pathogens by healthcare provider (HCP) clothing.design. We completed a 3-arm randomized controlled trial to test the efficacy of 2 types of antimicrobial-impregnated clothing compared to standard HCP clothing. Cultures were obtained from each nurse participant, the healthcare environment, and patients during each shift. The primary outcome was the change in total contamination on nurse scrubs, measured as the sum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
1
22
0
4
Order By: Relevance
“…The hands and clothing of health-care professionals regularly become contaminated by both the patient and the environment. 1719…”
Section: Discussionmentioning
confidence: 99%
“…The hands and clothing of health-care professionals regularly become contaminated by both the patient and the environment. 1719…”
Section: Discussionmentioning
confidence: 99%
“…However, silver was ineffective in reducing bacterial viability in a previous culture-based study that revealed no significant difference in colony-forming units of bacteria found on silverimpregnated surgical scrubs compared to cotton scrubs worn by healthcare providers. 10 According to the manufacturer of the screens, the antimicrobial properties are due to leaching of silver ions from the glass. 4 Thus, another explanation for the observed lack of difference could be that effective doses of silver were no longer being leached from the glass, thus it lost its antimicrobial properties by day 30.…”
Section: Discussionmentioning
confidence: 99%
“…However, little literature data are available concerning the effect of antimicrobial silvered/nanosilvered medical textiles in hospital settings in the aspect of the reduction of the prevalence of HAI-associated pathogens, and thus the reduction of HAI incidence. Of note, most articles were focused on their use in the hospital staff clothes to reduce their bacterial contamination and transmission [17][18][19][20].…”
Section: The Practical Use Of Antimicrobial Textiles In Healthcare Sementioning
confidence: 99%
“…In the data obtained during the Antimicrobial Scrub Contamination and Transmission (ASCOT) trial [20], antimicrobial-impregnated scrubs, including silver-containing cloths, were not effective at reducing bacterial contamination as compared to traditional cloths measured as the sum of colony-forming units (CFU) of bacteria identified on nurse scrubs from each clothing location. These studies enrolled nurses from medical and surgery intensive care units of the university hospital, and samples for microbiological analysis were collected during 3 consecutive 12-hour shifts in the intensive care unit.…”
Section: The Practical Use Of Antimicrobial Textiles In Healthcare Sementioning
confidence: 99%